2000
DOI: 10.1177/000331970005100602
|View full text |Cite
|
Sign up to set email alerts
|

Nonfilling of Contrast in Deep Leg Vein Isolated Nonfilling of Contrast in Deep Leg Vein Segments Seen on Phlebography, and a Comparison with Color Doppler Ultrasound, to Assess the Incidence of Deep Leg Vein Thrombosis

Abstract: Nonfilling of contrast in deep veins on phlebography is claimed to be an indirect sign of deep vein thrombosis (DVT) by some authors but rejected by others. The aim of this study was to prospectively assess, with color Doppler ultrasound (CDU), the occurrence and distribution of DVT in isolated, nonfilling, deep vein segments seen on a phlebogram. One hundred consecutive patients with clinical signs of acute DVT, in whom phlebography displayed nonfilling of the posterior tibial veins and/or the deep calf muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…This is because nonfilling of contrast in deep veins on phlebography is claimed to be an indirect sign of DVT by some authors but rejected by others. Bjorgell et al 15 showed that isolated nonfilling of the posterior tibial and/or deep muscle veins of the calf found by phlebography may be an indirect sign of DVT but is equally commonly caused by other pathological conditions like edema, bleedings, ligament and muscle ruptures, Baker cysts, and superficial thrombophlebitis or arises without any detectable explanation.…”
Section: Discussionmentioning
confidence: 99%
“…This is because nonfilling of contrast in deep veins on phlebography is claimed to be an indirect sign of DVT by some authors but rejected by others. Bjorgell et al 15 showed that isolated nonfilling of the posterior tibial and/or deep muscle veins of the calf found by phlebography may be an indirect sign of DVT but is equally commonly caused by other pathological conditions like edema, bleedings, ligament and muscle ruptures, Baker cysts, and superficial thrombophlebitis or arises without any detectable explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Though nonfilling of contrast in deep veins on venography has been accepted as an indirect sign of DVT, Björgell et al . (2000) showed that isolated nonfilling of posterior tibial and deep muscle veins of the calf seen on venography can equally be caused by other pathological conditions like edema, bleeding, ligaments and muscle rupture, Baker's cyst, and superficial thrombophlebitis, or arises without any detectable explanation, thereby leading to an exaggerated number of patients with thrombosis in these studies 15. Nowadays, duplex ultrasonography has become the diagnostic standard in most of the hospitals in the United States, making it more representative of real-time medical management 16.…”
Section: Discussionmentioning
confidence: 95%
“…However, isolated nonfilling of deep veins below the knee on phlebography was, in a recent study, successfully evaluated by subsequent color duplex sonography in 100 of 102 consecutive patients. 25 In conclusion, among patients with clinically suspected DVT and inconclusive duplex results, the number of indeterminate phlebographic findings is high, which reduces the utility of phlebography in this category of patients. Even if duplex examination findings are equivocal, it is still possible to extract clinically useful information by categorizing the duplex results into subgroups with low, intermediate, and high probability of DVT.…”
Section: Discussionmentioning
confidence: 97%